2006
DOI: 10.1007/s11243-006-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the interaction of thioglycolic acid with [(H2O)(tap)2RuORu(tap)2(H2O)]2+ ion at physiological pH

Abstract: The interaction of thioglycolic acid (tgaH 2 ) with the title complex has been studied spectrophotometrically in aqueous medium as a function of [substrate complex], [ligand], pH and temperature at constant ionic strength. The reactivity of different donor centers [e.g., (N), (N,O) and (O,O) are compared].In the studied pH range the reaction is a two-step ligand dependent process. The thermodynamic and activation parameters are reported and compared with other systems studied earlier. As no study on this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…The high negative Δ S ≠ values suggest a more compact transition state, where both the incoming and departing ligands are attached in the transition state, and this is also in support of the assumption of a ligand‐participated transition state. The Δ H ≠ and Δ S ≠ values have a good agreement with the previously studied systems 25–29 that also substantiate our study.…”
Section: Resultssupporting
confidence: 91%
“…The high negative Δ S ≠ values suggest a more compact transition state, where both the incoming and departing ligands are attached in the transition state, and this is also in support of the assumption of a ligand‐participated transition state. The Δ H ≠ and Δ S ≠ values have a good agreement with the previously studied systems 25–29 that also substantiate our study.…”
Section: Resultssupporting
confidence: 91%
“…The high negative S = values suggest a more compact transition state, where both the incoming and departing ligands are attached in the transition state, and this is also in support of the assumption of a ligand participated transition state. The H = and S = values are in good agreement with the previously studied systems [48][49][50][51][52] that also substantiate our study.…”
Section: Effect Of Temperaturesupporting
confidence: 92%
“…Initially, it is curved and shows linear behavior in the latter stage. The rate constants were calculated using the method of Weyh and Hamm [15] as described in an earlier paper [1] using the following equation:…”
Section: Kineticsmentioning
confidence: 99%
“…Ruthenium complexes are an order of magnitude less toxic than cisplatin, and aqua complexes if used directly will be less toxic as some hydrolyzed side products are responsible for toxicity. From a literature survey [1][2][3], it is revealed that many potential alternative metallopharmaceuticals have been developed, ruthenium being one of the most promising, and are currently undergoing clinical trials [4][5][6][7]. Another point of interest is that DNA is not the only target.…”
Section: Introductionmentioning
confidence: 99%